Evaluation of injection capabilities of a biopolymer based grout material - Lee, Minhyeong; Im, Jooyoung; Chang, Ilhan; Cho, Gye Chun (Geomechanics and Engineering, 2021)
Injection grouting is one of the most common ground improvement practice to increase the strength and reduce the hydraulic conductivity of soils. Owing to the environmental concerns of conventional grout materials, such as cement-based or silicate-based materials, bio-inspired biogeotechnical approaches are considered to be new sustainable and environmentally friendly ground improvement methods. Biopolymers, which are excretory products from living organisms, have been shown to significantly reduce the hydraulic conductivity via pore-clogging and increase the strength of soils. To study the practical application of biopolymers for seepage and ground water control, in this study, we explored the injection capabilities of biopolymer-based grout materials in both linear aperture and particulate media (i.e., sand and glassbeads) considering different injection pressures, biopolymer concentrations, and flow channel geometries. The hydraulic conductivity control of a biopolymer-based grout material was evaluated after injection into sandy soil under confined boundary conditions. The results showed that the performance of xanthan gum injection was mainly affected by the injection pressure and pore geometry (e.g., porosity) inside the soil. Additionally, with an increase in the xanthan gum concentration, the injection efficiency diminished while the hydraulic conductivity reduction efficiency enhanced significantly. The results of this study provide the potential capabilities of injection grouting to be performed with biopolymer-based materials for field application.
Keywords: Environmental concerns; Field application; Flow channel geometries; Ground improvement; Injection efficiency; Injection pressures; Potential capability; Reduction efficiency; Biopolymer; Hydraulic conductivity; Hydrogel; Injection grouting; Penetrability